018 The breast cancer, early disease: toxicity from therapy with epirubicin regimens ¨ c cardiac assessment and risk evaluation (better-care), cardiovascular magnetic resonance (CMR) sub-study: cycle 1 changes predict late anthracycline cardiotoxicity. (16th May 2012) - Smith, G C; Kotwinski, P; Sanders, J; Cooper, J; Ma, L; Jones, A; Mythen, M G; Montgomery, H E; Pennell, D J
Abstract : Introduction: A growing number of patients are at risk from chronic anthracycline cardiotoxicity (cAC) as a result of improving prognosis of cancer. This is true even at low, adjuvant doses. In breast cancer, Herceptin use increases this risk. Susceptibility is highly idiosyncratic. Although detection of cardiomyocyte injury using endomyocardial biopsy is the gold standard, it is not appropriate for routine monitoring. Serial measurements of LV ejection fraction (LVEF) only detect cardiotoxicity after significant damage has been incurred. Cardiovascular magnetic resonance (CMR) can detect myocardial inflammation and oedema using STIR (Short TI Inversion Recovery) and early gadolinium relative enhancement (EGRE). We hypothesised these CMR sequences could be used as non-invasive tests to assess acute injury and predict cAC. Methods: Patients receiving adjuvant chemotherapy for early breast cancer, were scanned before and 3 days after their first cycle of epirubicin. Follow-up CMR was performed >1 year after the final dose of anthracycline, or >3 months after the end of Herceptin. Cine imaging was used to measure LVEF; STIR and EGRE images were obtained to assess cardiac inflammation. Results: 51 patients completed the protocol. Changes in CMR parameters are outlined in the Abstract 018 table 1 below. In patients with a ¡Ý5% decrease in LVEF (n=22) at follow-up, the day 3 mean EGRE increased by 32% (p=0.002) and mean STIR SI increased by 15% (p=0.003). In the remaining patients (n=29) there were no significant changes in EGRE or STIR. Conclusions/Implications: This study has shown that subclinical myocarditis occurring after the first exposure to anthracycline can be detected using CMR and is associated with late falls in LVEF. Thus potentially identifying those at increased risk of premature heart failure, before the majority of damage is caused. Recognition of this susceptibility could inform treatment decisions and/or identify those requiring greater cardiac surveillance.